1991
DOI: 10.1111/j.1468-2958.1991.tb00245.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress and Gender on Nonverbal Decoding Accuracy in Kinesic and Vocalic Channels

Abstract: Stress has the potential to impair accurate decoding of others' communicntion. This expm'ment tested the effects of stress, induced through the S t m p Color-Word Test, on the accurate decoding of kinesic and vocalic emotional expressions. Respondents (N = 372) viewed or heard 30 emotional expressions interspersed with multichannel color stimuli that were redundant with one another (lour stress) or conflicted with oneanother (high stress). Analyses of accuracy scores across three triuls supported three of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Attunement requires the ability to accurately decode social stimuli. Experimental evidence suggests that decoding abilities are negatively affected by stress and depression (e.g., Keeley-Dyreson et al, 1991;Gur et al, 1992). This decreased ability may have affected the patients' competence to attune their support seeking behavior to the support giving behavior in the present experiment.…”
Section: Discussionmentioning
confidence: 67%
“…Attunement requires the ability to accurately decode social stimuli. Experimental evidence suggests that decoding abilities are negatively affected by stress and depression (e.g., Keeley-Dyreson et al, 1991;Gur et al, 1992). This decreased ability may have affected the patients' competence to attune their support seeking behavior to the support giving behavior in the present experiment.…”
Section: Discussionmentioning
confidence: 67%
“…However, most of the research assessing predictive validity (in meta-analyses controlling for other important factors) has focused on specific measures of EI, whether as integrated EI abilities or self-report trait or "mixed" models. tion recognition (Keeley-Dyreson, Bailey, & Burgoon, 1991).…”
Section: Principle 1: Dual Processes Govern Human Thought Feeling Amentioning
confidence: 99%
“…Comprehensive coding of relational information depends heavily on coder nonverbal sensitivity, which is highly variable, often resulting in low intercoder reliability (Keeley-Dyreson, Burgoon, & Bailey, 1991). However, communication researchers have shown that coding single nonverbal cues (e.g., smile, eye contact) is less meaningful than coding clusters of cues that suggest an affective quality (e.g., affiliation, dominance) (D.B.…”
Section: Relational Communication In Health Communication Coding and mentioning
confidence: 99%